Possibilities and limitations of local economic development in Serbia - Aničić Dušan; Gligorijević Jasmina; Jelić Miloje A.; Stojanović Milosav (Trendovi u Poslovanju)
The practice in developed countries has shown a necessity for local government's stronger inclusion in local economic development issues. The economic system in Serbia has features of high unemployment rate and low living standard among the population, and therefore local government taking a larger part in local economic development issues is seen as a real possibility for reducing these problems. Although most of the economic policy instruments lie within the central government jurisdiction, which largely restricts local government possibilities, there is still an important area for local government influence on economic development. There are numerous obstacles for a successful application of the local economic development concept in Serbia, which causes the municipality and regional potentials to be used much less than the possibilities allow, and it has a negative reflection, especially in rural and undeveloped areas.